Differential osteogenic potential of human adipose-derived stem cells co-cultured with human osteoblasts on polymeric microfiber scaffolds - Rozila, Ismail; Azari, Pedram; Munirah, Sha'ban; Wan Safwani, Wan Kamarul Zaman; Gan, Seng Neon; Nur Azurah, Abdul Ghani; Jahendran, Jeevanan; Pingguan-Murphy, Belinda; Chua, Kien Hui (Wiley, 2015)
The osteogenic potential of human adipose-derived stem cells (HADSCs) co-cultured with human osteoblasts (HOBs) using selected HADSCs/HOBs ratios of 1:1, 2:1, and 1:2, respectively, is evaluated. The HADSCs/HOBs were seeded on electrospun three-dimensional poly[(R)23-hydroxybutyric acid] (PHB) blended with bovine-derived hydroxyapatite (BHA). Monocultures of HADSCs and HOBs were used as control groups. The effects of PHB–BHA scaffold on cell proliferation and cell morphology were assessed by AlamarBlue assay and field emission scanning electron microscopy. Cell differentiation, cell mineralization, and osteogenic related gene expression of co-culture HADSCs/HOBs were examined by alkaline phosphatase (ALP) assay, alizarin Red S assay, and quantitative real time PCR, respectively. The results showed that co-culture of HADSCs/HOBs, 1:1 grown into PHB–BHA promoted better cell adhesion, displayed a significant higher cell proliferation, higher production of ALP, extracellular mineralization and osteogenic-related gene expression of run-related transcription factor, bone sialoprotein, osteopontin, and osteocalcin compared to other coculture groups. This result also suggests that the use of electrospun PHB–BHA in a co-culture HADSCs/HOBs system may serve as promising approach to facilitate osteogenic differentiation activity of HADSCs through direct cell-to-cell contact with HOBs.